(untitled) (Research, Society and Development, 2022)
Study with the objective of identifying the number of adherence and abandonment of leprosy treatment in the State of Sergipe through the records available in the computer department of SUS (DATASUS). This is an epidemiological study of the ecological type with territorial basis of analysis the seven health regions of the State of Sergipe: Aracaju, Estância, Itabaiana, Lagarto. Nossa Senhora de Lourdes, Nossa Senhora do Socorro and Propriá. The search included studies published in English and Portuguese available in the Scielo, Lilacs and PubMed databases, using the descriptors "Leprosy", "Public Health", "Pharmacological treatment" with the Boolean operator "and". A total of 16,232 doses administered in the period 2016-2020 were identified, Aracaju is the region with the highest number of treatment abandonment with (67%) of cases, the lowest number is registered in the region of Nossa S. da Glória with 1 case (0.2%). Regarding adherence, men were the ones who adhered the most (59%). Thus, health education actions are necessary, clear guidelines that place the individual as the protagonist of their treatment.